Incentive effects on risk attitude in small probability prospects - Mathieu Lefèbvre; Ferdinand M. Vieider; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2009)
Most studies on the role of incentives on risk attitude report data obtained from within-subject experimental investigations. This may however raise an issue of sequentiality of effects as later choices may be influenced by earlier ones. This paper reports instead between-subject results on the effect of monetary stakes on risk attitudes for small probability prospects in a laboratory experiment. Under low stakes, we find the typical risk seeking behavior for small probabilities predicted by the prospect theory. But under high stakes, we provide some evidence that risk seeking behavior is dramatically reduced. This could suggest that utility is not consistently concave over the outcome space, but rather contains a convex section for very small amounts.
Keywords: C91; D81; D89; 330; Risk attitude; incentives; decision; experiment; Risikopräferenz; Ökonomischer Anreiz; Prospect Theory; Entscheidung bei Unsicherheit; Test